Invasive hemodynamic monitoring by Swan-Ganz pulmonary artery catheter: concepts and utility - Carrasco Rueda, José María (2021)
Since its beginnings in the last century, pulmonary artery catheterization (PAC) has evolved into an invasive hemodynamic evaluation technique that can be performed at the patient’s bedside through a Swan-Ganz catheter; this procedure has maintained an intermittent course in terms of its use; however, it has currently demonstrated relevance in specific scenarios. The PAC allows access to the central venous circulation, the right heart and the pulmonary artery; it performs the calculation of hemodynamic variables directly or indirectly by means of established formulas and methods. This makes possible to perform an adequate hemodynamic evaluation and classification, perform specific tests (e.g. vasoreactivity test), which help to define the diagnosis, therapeutic , monitor the response to treatment, evaluation prior to advanced therapies (e.g. cardiac transplantation or mechanical circulatory assistance devices), and prognosis in our patients. In this article we discuss the concepts and usefulness of pulmonary artery catheterization.